2021
DOI: 10.3390/ijms22041757
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Transformation of Somatic Embryos and Regeneration of Cork Oak Plantlets with a Gene (CsTL1) Encoding a Chestnut Thaumatin-Like Protein

Abstract: We present a reproducible procedure for transforming somatic embryos of cork oak with the CsTL1 gene that codes for a thaumatin-like protein, in order to confer tolerance to Phytophthora cinnamomi. Different concentrations/combinations of the antibiotics carbenicillin and cefotaxime, as bacteriostatic agents, and kanamycin, as a selective agent, were tested. A lethal dose of 125 mg/L kanamycin was employed to select transgenic somatic embryos, and carbenicillin was used as a bacteriostatic agent at a concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 94 publications
(131 reference statements)
0
13
0
Order By: Relevance
“…This type of material has already been suggested to be the most suitable target tissue for the transformation of several woody species such as Vitis rotundifolia [ 38 ], C. dentata [ 39 ] and Coffea arabica [ 36 ]. As in other transformation systems [ 19 , 39 , 40 ], transformation efficiency in holm oak is affected by the genotype of the embryogenic lines, and transformation was only obtained in two of the four lines evaluated. Although the transformation efficiency was low (2.5%), it was similar to the values reported in a previous paper (1.66–3.33%) on holm oak genetic transformation [ 18 ].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This type of material has already been suggested to be the most suitable target tissue for the transformation of several woody species such as Vitis rotundifolia [ 38 ], C. dentata [ 39 ] and Coffea arabica [ 36 ]. As in other transformation systems [ 19 , 39 , 40 ], transformation efficiency in holm oak is affected by the genotype of the embryogenic lines, and transformation was only obtained in two of the four lines evaluated. Although the transformation efficiency was low (2.5%), it was similar to the values reported in a previous paper (1.66–3.33%) on holm oak genetic transformation [ 18 ].…”
Section: Discussionmentioning
confidence: 90%
“…Somatic embryogenesis is considered the best regeneration method for producing transgenic plants in hardwood species as the regeneration capacity is higher and the incidence of chimera is lower than in other regeneration methods [ 15 ]. Recent progress in Agrobacterium tumefaciens -mediated genetic transformation of somatic embryos of different species in the Fagaceae family, including holm oak, have provided the opportunity to produce transgenic genotypes [ 16 , 17 , 18 , 19 ]. These studies have investigated overexpression of the pathogenesis-related thaumatin-like protein in order to induce tolerance to P. cinnamomi .…”
Section: Introductionmentioning
confidence: 99%
“…Genotype is considered the determinant factor in the success of this process in plant species because protocols suitable for one embryogenesis line or clones may not necessarily apply to others (Petri and Burgos, 2005). Only one or two EC genotypes were developed in previous genetic transformation protocols of woody plants, such as Paulownia elongata (Bajaj et al, 2021), olive (Olea europaea L.) (Narvaez et al, 2019;Palomo-Rios et al, 2021), Cork oak (Quercus suber L.) (Alvarez et al, 2004;Cano et al, 2021), European chestnut (Corredoira et al, 2016), and tea (Camellia sinensis) (Mondal et al, 2001). In this study, we obtained five EC genotypes, including two types of EC initiated from mature seed explants and three types from stem segment explants, which indicated that our constructed EC protocol was independent of genotype; therefore, it might be able to be extended to elite cultivars.…”
Section: Multiple Genotypes and Multiple Explantmentioning
confidence: 99%
“…The transformed explants ranged from shoot apices (Ceasar et al, 2017), stem internodes (Confalonieri et al, 2000), axillary buds (Maheshwari and Kovalchuk, 2016), and leaves (Confalonieri et al, 1994;Yang et al, 2016;Song et al, 2019) to EC and somatic embryos from specific starting explants (Corredoira et al, 2016;Sood et al, 2020;Cano et al, 2021). First, the use of vegetative tissues and organs, such as leaf and stem internodes, had the disadvantages of chimeric transgenic plant production and low transformation efficiency.…”
Section: Multiple Genotypes and Multiple Explantmentioning
confidence: 99%
See 1 more Smart Citation